Postural control in elite decathlon athletes: are various modes of dynamic assessment needed? - Reuter, S.; Forkel, P.; Imhoff, A. B.; Beitzel, K. (The Journal of Sports Medicine and Physical Fitness, 2017)
BACKGROUND: Decathlon consists of various track and field running, jumping and throwing events. This results in high physical demands and poor postural control may predispose athletes at a higher risk for injury. The purpose of this study was to measure and to show a relationship of different dynamic postural control tests in healthy professional decathlon athletes.